Peningkatan Penalaran Penyelesaian Soal Higher Order Thinking dalam Pembelajaran Matematika SMP melalui Model ECGV - Enung Sumarni; Theresia Widyantini (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2019)
The aim of this research is: 1) identifying the condition of teaching and learning in the classroom applying ECGV learning model; 2) comparing the improvement of higher order thinking skill when ECGV learning model is applied and without the ECGV learning model; 3) examining the efforts to improve the influencing factors of students’ higher order thinking skills. This study applies quantitative approach with a rationalistic paradigm. At first, this study described the condition of the controlling class, in which students were learning as usual, as well as experimental class carried out applying the ECGV model (Exploration, Conjecture, Generalization, and Verification). Different treatments were applied to the controlling and experimental classes to have the difference in normalized gain values to indicate an improvement of the achievement in this learning stage. The research results indicates that: 1) ECGV model is an effective learning model to improve skills within the learning process as well as students' thinking skills; 2) The ECGV stages should be applied from stages 1 to 4 accordingly, considering some factors that should be the focus for improvement; 3) Learning result indicated by in students' thinking abilities in the lower class increases greater than the higher class; 4) Some determining factors in the improvement of students' reasoning skills are found; class climate (environment, teacher and school), student psychology, and student intellectuals.